Remifentanil for Procedural Sedation and Analgesia in Central Venous Catheter Insertion: A Randomized, Controlled Trial. Issue 8 (August 2019) - Vardon Bounes, Fanny; Pichon, Xavier; Ducos, Guillaume; Ruiz, Jean; Samier, Caroline; Silva, Stein; Sommet, Agnès; Fourcade, Olivier; Conil, Jean-Marie; Minville, Vincent
Abstract : Objective: Central venous catheter (CVC) insertion is a common practice for anesthetists, but this invasive procedure generates anxiety and pain in patients that are often underestimated. We compared target-controlled infusion of remifentanil and local lidocaine infiltration with placebo and local lidocaine infiltration to decrease pain scores during CVC placement. Materials and Methods: We included conscious, adult patients without contraindication to remifentanil or lidocaine. We excluded pregnant women, emergency situations, and opioid abuse. Patients requiring CVC were randomly assigned, using computer-generated allocation numbers stored in sealed envelopes, to receive target-controlled infusion of remifentanil or placebo—all patients received local anesthesia with lidocaine. All patients were hospitalized in a recovery room or intensive care unit, monitored, and received 4 L/min of oxygen. The primary outcome was global pain (Verbal Numeric Rating Pain Scale) during the procedure. Secondary outcomes were pain perceived at every stage of the procedure, anxiety, patient satisfaction, operational ease, and side effects. Results: In this double-blind study, we included 90 patients (split into 2 groups of 45 patients). Global pain was significantly reduced in the remifentanil group: 20 of 100 (95% confidence interval, 16-40) versus 50 of 100 (95% confidence interval, 40-60) in the placebo group; P =0.0009. No major adverse events were observed during this study, and there were no significant differences between both groups regarding side effects. Discussion: Target-controlled infusion of remifentanil is an effective drug to reduce pain during CVC insertion in association with lidocaine-based local anesthesia, in conscious patients.